NOTES ON EGGS, LARVAE AND JUVENILES OF FISHES FROM INDIAN WATERS Vni. Scomberomorus gutiatus (Bloch and Schneider), IX. Scomberomorus commerson (Lacepede) and X. Scomberomorus lineolatus (Cuvier - Jones, S (Indian Journal of Fisheries, 2011)
THIS is the commonest seerfish in Indian waters and is fairly widely distributedin the Indo-Pacific from the Persian Gulf in the east to the Western Pacificfrom Taiwan to Indonesia. It attains a length of about | of a metre. Accordingto Munro (1943) S. guttatus does not occur in Australian waters and thespecimens formerly identified as S. guttatus were most likely either S. queenH'landicus or 5. semifasciatus. Some may even refer to S. niphonius